Why do birds suddenly appear?: mapeando o risco aviário no entorno dos aeroportos da Região Metropolitana de Belo Horizonte - Matheus Miranda da Silva (2018)
Attention to the safety of air travel requires the focus on several issues related to this event, such as the collision of aircraft with animals, mainly birds. Of the several causes of this phenomenon, we highlight the land cover in the surroundings of the airports as a potential factor of attraction of these species to the local, aggravating the safety problem. However, the relationship between land cover patterns and the risk of collision between aircraft and birds is still a gap in the literature, and needs to be investigated to support public policy. This work aims to determine the factors with potential for attracting birds in the main airports of the metropolitan area of Belo Horizonte - MG, using environmental analysis techniques and geospatial tools. Spatial analysis involving the mapping of land use and determination of other environmental variables were used to calculate the attractiveness of birds in the different aerodromes studied. In addition, statistical analysis were used to analyze the security radii of airports. With the results of the study, it was possible to elucidate the relationships among landscape structure, vegetation density and its associations with areas of high and low potential for attracting birds, as well as discussing the determination of areas of safety and planning for the risk aviary. It has been observed that aerodrome safety radius efficiency is dependent on the conditions of land use around airports, and such factors must be observed in airport security planning.